Studio della gestione integrata dei rifiuti urbani nell'ambito della provincia di Bologna - Nanni, Marcella <1980> (Alma Mater Studiorum - Università di Bologna, 2009)
This work is an analysis of integrated urban waste management in the province of Bologna. It consists of five chapters and one enclosure. Primarily, it focuses on the legislative framework at european, national and local level. Then the study analyses the situation of urban waste system adopted in the reference territory from 2003 to 2007 to show its evolution process. Chapter 3 is based on considerations about the percentage of effective recover of materials derived from separate collection that has been reached in the province of Bologna in 2006. The following chapter describes the urban waste management at national level using dates of 2005 and 2006 by APAT (National Agency for environmental protection). Then, it has been made a comparison with Emilia-Romagna and district of Bologna. Chapter 5 focuses on the description of innovative strategies introduced in the district of Bologna to increase separate collection level and optimize waste management. In particular, it analyses two sperimental projects: one based on door to door collection and the other founded on an integrated collection system which provides the application of two collection models (door to door collection in industrial areas and collection by containers in urban ones). Finally, in the enclosure, it is also descrided best practices of waste management sector about collection models, treatment plants and innovative strategies available at that moment in Europe.